UJI AKTIVITAS ENZIM DEHIDROGENASE LAKTAT (DHL) YANG TERENKAPSULASI DALAM SILIKA DARI ABU SEKAM PADI - Noor Hindryawati (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2011)
A research has been conducted in testing the enzymatic activity of the encapsulated Lactate dehydrogenase (LDH) in silica by sol-gel process using sodium silicate from rice hull ash. The encapsulation was carried out by mixing sodium silicate (Na2SiO3) sol solution and phosphate buffer pH 7 containing both LDH enzyme and coenzyme of nicotinamide adenine dinucleotide (NAD+). After 2-6 minute of shaking, the mixture was then transferred into a 96-microwell plate and stored overnight. The encapsulation activity of encapsulation product was quantified by measuring absorption of NADH, as coenzyme hydrogenation product, at 340 nm utilizing an ELISA (Enzyme Linked Immunosorbent Assay) reader. For comparison similar experiment was also carried out for free enzyme. The result of the research shows that the kkat for encapsulated LDH enzyme (ET) is smaller than free enzyme (EB), which means that the encapsulation enzyme will affect the velocity of product reaction. The velocity of the encapsulation enzyme (ET) reaction is lower than free enzyme (EB) as the consequence of weak interaction between the substrate and enzyme or influenced by k1.